MRB10130 is a RESC assembly factor that promotes kinetoplastid RNA editing initiation and progression - McAdams, Natalie M. (RNA, 2019)
Uridine insertion deletion editing in kinetoplastid protozoa requires a complex machinery, a primary component of which is the RNA editing substrate binding complex (RESC). RESC contains two modules termed GRBC (guide RNA binding complex) and REMC (RNA editing mediator complex), although how interactions between these modules and their mRNA and gRNA binding partners are controlled is not well understood. Here, we demonstrate that the ARM/HEAT repeat containing RESC protein, MRB10130, controls REMC association with mRNA- and gRNA-loaded GRBC. High-throughput sequencing analyses show that MRB10130 functions in both initiation and 3′ to 5′ progression of editing through gRNA-defined domains. Editing intermediates that accumulate upon MRB10130 depletion significantly intersect those in cells depleted of another RESC organizer, MRB7260, but are distinct from those in cells depleted of specific REMC proteins. We present a model in which MRB10130 coordinates numerous protein–protein and protein–RNA interactions during editing progression.